2006
DOI: 10.1158/1078-0432.ccr-06-0569
|View full text |Cite
|
Sign up to set email alerts
|

Axillary Lymph Node Nanometastases Are Prognostic Factors for Disease-Free Survival and Metastatic Relapse in Breast Cancer Patients

Abstract: Purpose: Early breast cancer presents with a remarkable heterogeneity of outcomes.Undetected, microscopic lymph node tumor deposits may account for a significant fraction of this prognostic diversity. Thus, we systematically evaluated the presence of lymph node tumor cell deposits V0.2 mm in diameter [pN 0(i+) , nanometastases] and analyzed their prognostic effect. Experimental Design: Single-institution, consecutive patients with 8 years of median follow-up (n = 702) were studied. To maximize chances of dete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 33 publications
3
78
0
Order By: Relevance
“…However, their findings are consistent with the 14.7% non-SLN rate identified by the European Institute of Oncology, which found the prevalence of SLN ITC to be 9.4% (116 patients) [29,56]. SLN tumour burden emerged as a significant predictor of non-SLN involvement, which again was Querzoli et al [61] found ITC to be prognostic indicators of DFS and metastatic relapse. After a median follow-up of 8 years, the HR for all adverse events of pN0i+ compared to node negative patients was 2.51 (p <0.05).…”
Section: Evidence In Favoursupporting
confidence: 82%
See 1 more Smart Citation
“…However, their findings are consistent with the 14.7% non-SLN rate identified by the European Institute of Oncology, which found the prevalence of SLN ITC to be 9.4% (116 patients) [29,56]. SLN tumour burden emerged as a significant predictor of non-SLN involvement, which again was Querzoli et al [61] found ITC to be prognostic indicators of DFS and metastatic relapse. After a median follow-up of 8 years, the HR for all adverse events of pN0i+ compared to node negative patients was 2.51 (p <0.05).…”
Section: Evidence In Favoursupporting
confidence: 82%
“…Indeed, the current distinction between ITC and MM seems to have little significance in predicting non-SLN involvement or prognosis [29,57,58,61].…”
Section: Discussionmentioning
confidence: 99%
“…Patients were selected according to the following criteria: tumor diameter: T1, T2; absence of nodal diffusion (23,24); absence of distant metastases at diagnosis. Clinical and pathologic status, tumor histotype, histologic grade, levels of expression of estrogen receptor a and progesterone receptor (PGR), and fraction of proliferating cells (% Ki-67) were recorded (25).…”
Section: Tumor Patient Case Seriesmentioning
confidence: 99%
“…Lobular metastases are particularly challenging for conventional, sampling-based histologic methods because they are often distributed as diminutive clusters or single cells. There is growing consensus that such metastatic deposits should be counted as node positive, even when none is >.2 mm, when a substantial amount of the node is so involved [11].…”
Section: Introductionmentioning
confidence: 99%